Potential interactions between diatoms and bacteria are shaped by trace element gradients in the Southern Ocean - Sterling, Alexa R.; Holland, Laura Z.; Bundy, Randelle M.; Burns, Shannon M.; Buck, Kristen N.; Chappell, P. Dreux; Jenkins, Bethany D. (Frontiers in Marine Science, 2023)
The growth of diatoms in the Southern Ocean, especially the region surrounding the West Antarctic Peninsula, is frequently constrained by low dissolved iron and other trace metal concentrations. This challenge may be overcome by mutualisms between diatoms and co-occurring associated bacteria, in which diatoms produce organic carbon as a substrate for bacterial growth, and bacteria produce siderophores, metal-binding ligands that can supply diatoms with metals upon uptake as well as other useful secondary compounds for diatom growth like vitamins. To examine the relationships between diatoms and bacteria in the plankton (diatom) size class (> 3 µm), we sampled both bacterial and diatom community composition with accompanying environmental metadata across a naturally occurring concentration gradient of macronutrients, trace metals and siderophores at 21 stations near the West Antarctic Peninsula (WAP). Offshore Drake Passage stations had low dissolved iron (0.33 ± 0.15 nM), while the stations closer to the continental margin had higher dissolved iron (5.05 ± 1.83 nM). A similar geographic pattern was observed for macronutrients and most other trace metals measured, but there was not a clear inshore-offshore gradient in siderophore concentrations. The diatom and bacteria assemblages, determined using 18S and 16S rDNA sequencing respectively, were similar by location sampled, and variance in both assemblages was driven in part by concentrations of soluble reactive phosphorous, dissolved manganese, and dissolved copper, which were all higher near the continent. Some of the most common diatom sequence types observed were Thalassiosira and Fragilariopsis, and bacteria in the plankton size fraction were most commonly Bacteroidetes and Gammaproteobacteria. Network analysis showed positive associations between diatoms and bacteria, indicating possible in situ mutualisms through strategies such as siderophore and vitamin biosynthesis and exchange. This work furthers the understanding of how naturally occurring gradients of metals and nutrients influence diatom-bacteria interactions. Our data suggest that distinct groups of diatoms and associated bacteria are interacting under different trace metal regimes in the WAP, and that diatoms with different bacterial partners may have different modes of biologically supplied trace metals.